The yield of Jerusalem artichoke plant Helianthus tuberosus L. grown in various combinations of fertilisation – preliminary research - Joanna Puła; Angelika Kliszcz (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2017)
Jerusalem artichoke is a perennial plant, which originates from North America. Tubers are characterised by high nutritional and energy values and can therefore be a source of food for humans and animals. The interest in tubers of Helianthus tuberosus L. in the diet of man is primarily due to the content of inulin and fructooligosaccharides, minerals, vitamins, and amino acids in them. In addition, it is a plant that is not demanding in agrotechnical conditions. Hence, the interest in cultivation this plant has increased. The main objective of the experiment was to evaluate the effect of biochar on the average yield of tubers and some morphological characteristics of plants. The study was conducted in conditions of a field experiment in 2016 at the Experimental Station of the University of Agriculture in Kraków. Two varieties: ‘Albik’ and ‘Rubik’, were grown in the experiment with different fertilisation variants. Biochar from the coniferous wood industry and mineral fertilisers were used. The ‘Rubik’ variety yields better than the ‘Albik’ variety under tested soil conditions, and the combined use of biochar and the basic dose of mineral fertilisation gives the best yields in the cultivation of Jerusalem artichoke.